PAYMENT OF ENVIRONMENTAL PAYMENTS: PROBLEMS, PROSPECTS - B. H. Aliyev; M. D. Eldarusheva (Юг России: экология, развитие)
Abstract. Aim.The subject of the research are economic payments, their normative regulation, problems and perspectives. The aim of the research is to study and analyze the problems of ecological charges calculation and payment.Methods.The following scientific methods were used in this research: 1. Heuristic: collective notepad method, brainstorming, synectics method, case method. 2. Traditional: method of comparison; method of relative and comparative values; graphic method; group method. 3. Method of deterministic factors: the method of chain production; the method of absolute differences; the method of relative differences. 4. Methods of stochastic factor analysis: correlation and regression analysis; analysis of variance; analysis of compnents; multidimensional analysis. 5.Methods of optimized indicators: economic and mathematical methods; programming; the theory of mass examination; game theory; operations research. Innovative approaches. Data mining term is used to indicate the aggregate methods of information detection necessary to make decisions in different spheres of the economy; and it is also the software which allows to optimize and simplify the analysis procedure. The most widespread of them are: Vortex, SPSS, Statistica.Results.The terms of ecological charges are considered and generalized, the estimation of waste negative impact on the environment is given, the ecological legislation is analyzed, recommendations on basic and technical norms are given.The area of research results application may be the ecological legislation and its economic aspects.Main conclusions.The general order of payment calculation for the negative influence on the environment is used if users of natural resources beside the waste of business activity affect the Environment the other way: polluting stuff emission into the atmosphere or water objects.